Examining bacteriological and chemical drinking-water quality, sanitation, hygiene, and contamination risk levels in industries in Bishoftu Town, Ethiopia - Getachew Tollera; Aderajew Mekonnen Girmay (Discover Water)
Abstract Introduction Water plays a crucial role in various industrial and manufacturing processes, including drinking, cleaning, cooling, processing, and transporting products. Ensuring that the water used in these processes is of the highest quality is essential for supporting efficient operations, safeguarding the environment, and protecting public health. Despite the lack of comprehensive studies, it is suspected that in Bishoftu Town, Ethiopia, an emerging industrial center, the interplay between water quality, sanitation practices, and hygiene standards poses critical challenges. Therefore, addressing these concerns is vital for promoting safe industrial practices and enhancing the well-being of both workers and the local community. Methods A cross-sectional study was undertaken in the industries of Bishoftu Town. A systematic random sampling method was employed to select 78 industries. From each industry, drinking-water samples were collected directly from water storage facilities. A structured questionnaire and observational checklist were used to assess the sanitation and hygiene levels of the industries. The membrane filtering method was used to count the Escherichia coli (E. coli), Total Coliform, and Fecal Coliform. Nitrate concentration was determined using an ultraviolet spectrophotometer. Ion-Selective Electrode (ISE) testing was used to determine the fluoride levels in the drinking water. Descriptive statistics were conducted to analyze the data. Results Findings revealed that 13.9% of industrial drinking-water samples tested positive for total coliforms, 4.2% for fecal coliforms, and 2.8% were positive for E. coli. In this study, 12.5% of drinking water samples exceeded the WHO's permissible fluoride concentration of 1.5 mg/litre, and 76.4% of industries did not treat their drinking water at the source. Besides, 68.1% of sanitation facilities lacked menstrual hygiene services, and 42% of industries' handwashing facilities were without both water and soap. Conclusion Significant numbers of drinking-water samples tested positive for various water quality indicator bacteria, indicating potential contamination risks for human being. Additionally, a substantial proportion of samples exhibited fluoride concentrations exceeding permissible levels. Besides, many industries lacked handwashing facilities with water and soap accessible near the latrines. A large number of industries lacked at least one usable improved toilet for women that included menstrual hygiene facilities. These findings highlight the urgent need for improved water quality, better access to handwashing facilities, and improved toilets for women that include menstrual hygiene amenities.